Enhancing Botanical Literacy through Project-Based Learning with Botanipedia: A Study on Plant Diversity and Classification - Risma Perdila Anggaresta; Diana Hernawati; Rita Fitriani (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2025)
Botanical literacy among students remains relatively low, as reflected in recent studies highlighting students’ limited understanding and appreciation of plant diversity and its essential role in ecosystems and human life. This condition underscores the urgency to implement innovative learning strategies to improve students’ botanical literacy. This study aims to analyze the effect of the Project-Based Learning (PjBL) model assisted by Botanipedia media on students’ botanical literacy in plant diversity and classification. As part of biological literacy, botanical literacy includes knowledge, inquiry skills, and the ability to connect plant concepts to real-life contexts. This research applied a quasi-experimental design with a nonequivalent control group. The sample consisted of two Grade X classes at SMA Negeri 2 Tasikmalaya, selected through purposive sampling. Class X-1 (experimental group) was taught using PjBL assisted by Botanipedia, while class X-3 (control group) was taught using PjBL without additional media. Botanical literacy was measured using a 15-item multiple-choice test developed based on Uno and Bybee’s framework. Data were analyzed using Quade Rank Analysis of Covariance. The results showed a significant improvement in the experimental group compared to the control group (p = 0.031, p < 0.05). The integration of Botanipedia enhanced students’ botanical literacy across all indicators. These findings support using interactive media to strengthen botanical literacy through project-based learning.